PENGEMBANGAN MODUL PERENCANAAN STUDI LANJUT BAGI SISWA SMP/MTs - ARDI, ARDI (DIDAKTIKA, 2017)
The research is a research and development. The subjects of this research are the professional of education media, the professional of guidance and counseling, the guidance and counseling teacher or practical in the school and student. The technigue of collecting data are used with inquiri and interview the resultang from. This research of this development are (i) the description of result the level necessary guidance and counseling teachers and student about the development further study plan module indicate that the students need very much the module of the development of planning the study of continue. From inquiry result are got precentase level the necessary student in the amount 90,33%. (ii) The further study plan module for SMP/MTs student have passed validation test phase and acceptabilities by professional (the professional education media and guidance and counseling professional), and small group test by guidance and counseling teacher and students. With result for validating test by professional are got 3,19 on the average it is mean that are developed very valid. Meanwhile acceptability test (usability, feasibility, and accuracy) from the professional/expert subjects are got 3,41 on the average it is mean that very acceptable. While acceptability test (usability, feasibility, and accuracy) by the small grouf test (guidance teacher and students) obtained the average each 3,65 and 3,42 it is mean that very acceptable.